A New Inventory Model for Maintenance Organizations - Ramana Murthy, N. V. (Indian Journal of Marketing, 2009)
The concept of Economic ordering quantity is generally employed by Public/Private sector undertakings and Govt. organizations, trying to balance the opposing costs of Inventory carrying costs and ordering costs. This is a simplistic method, which does not directly take into account the month-wise consumption/utilization trends of spare parts used. This article focuses on a "New Inventory Model" based upon actual consumption trends of materials/spares in the immediate past and the ideal maintenance requirements of spares in a year for ensuring trouble-free service of machinery and plant for achieving zero defects/breakdowns. The month-wise fluctuations in drawals/utilizations are translated into a vision by introducing utilization ratio as ratio between the maximum and minimum of actual utilization during the year. Similar to growth of population, the procurement coefficient is arrived at as a geometric mean between theory and simulated practice, with utilization ratio as the common ratio. Finally Revised Annual Procurement (RAP) is found out by making use of this information. The new Inventory Model (NIM) is easy to understand, since it is based on ground realities and is amenable for computerization.